Condensation heat transfer and pressure drop of low GWP R-404A-alternative refrigerants (R-448A, R-449A, R-455A, R-454C) in a 7.0-mm outer-diameter horizontal microfin tube. (June 2021) - Kim, Cheol-Hwan; Kim, Nae-Hyun
Abstract: The literature shows that condensation study of R-404A-alternative refrigerants in a microfin tube is lacking. In this study, four R-404A-alternative refrigerants—two short-term (R-448A, R-449A) and two long-term refrigerants (R-455A, R-454C) including R-404A—were tested in a 7.0-mm outer-diameter microfin tube. Tests were conducted over a mass flux range of 80 to 400 kg m −2 s −1 . At a low mass flux (of up to 200 kg m −2 s −1 ), the heat-transfer coefficients of the alternative refrigerants were 25–31% lower than those of R-404A. As the mass flux increased to 400 kg m −2 s −1, the heat-transfer coefficients of the alternative refrigerants were similar to those of R-404A. Of the alternative refrigerants, the long-term refrigerants (R-455A, R454C) yielded 1.2–32% smaller heat-transfer coefficients than the short-term refrigerants (R-448A, R-449A), due to larger (by 46–126%) temperature glides. On the other hand, the pressure drops of alternative refrigerants were 18–205% larger than those of R-404A. Long-term refrigerants (R-454C, R-455A) yielded 14–64% larger pressure drops than short-term refrigerants (R-448A, R-449A), likely due to a smaller vapor density. The enhancement ratios ( hmicro /hsm : heat transfer coefficient of the microfin tube over that of the smooth tube) of the alternative refrigerants varied from 1.24 to 1.89. The penalty factors [ dP/dz)f, micro /dP/dz)f, sm: frictional pressure drop of the microfin tube over that of the smooth tube] ranged from 1.03 to 3.17, showing a wide variation among refrigerants. A comparison with existing correlations revealed that the correlation of Kedzierski and Goncalves (1999) predicted 76% of the heat-transfer coefficients and that of Nozu et al. (1998) predicted 73% of the frictional pressure drops within ± 30.0%.